Statistical Analysis of Hydrodynamic Forces in Power-Law Fluid Flow in a Channel: Circular Versus Semi-Circular Cylinder - Mahmood, Rashid; Majeed, Afraz Hussain; Tahir, Muhammad; Saddique, Imran; Hamadneh, Nawaf N.; Khan, Ilyas; Mehmood, Asif (Frontiers in Physics, 2022)
This numerical study is about the steady of incompressible fluid flow in a channel with static obstacles. The flow field is governed by the Generalized Navier-Stokes equation incorporating the constitutive relation of Power-Law fluids. Three cases are considered (i). Circular obstacle (ii) semicircular obstacle (iii). Both circular and semicircular obstacles. A range of values of the Power-law index 0.2